Themes of Parole as Presented in Bill C-10: Contributing to the Conservative Government's 'Tough on Crime' Approach to the Criminal Justice System? - Lynch, Michael (Université d'Ottawa / University of Ottawa, 2015)
Canada’s federal prison population has been rising for the past 10 years. This is perplexing given Canada’s national official crime rate has been declining since the 1970’s. One possible explanation for the rising prison population could be related to the restrictive measures imposed on parole policies during the last forty years. This thesis intends to analyze the recent parliamentary discourses surrounding recent legislative changes brought to parole by the conservative government. In doing so, a document analysis is conducted on the Parliamentary debates pertaining to section 6 and section 7 of Bill C-10 as well as the content of the amendments within section 6 and section 7 of Bill C-10. The purpose of the document analysis is to analyze the themes within these documents and determine whether or not these themes represent a potential change in the punitive approach towards parole. Given that a more punitive approach could have negative impacts on certain offenders and on society in general, this thesis aims to better understand the discourses and values of the Parliamentary debate participants’ changes to the legislation and the potential impacts these restrictions may have for Canada’s federal prison population.
Keywords: Parole; Parliamentary Debates; Document Analysis; 'Tough on Crime'